Implementation of History Teachers in Implementing the 2013 Curriculum in Class X at SMA N 1 Rembang Academic - Sutarman, Eko (Universitas Negeri Semarang, 2018)
This study used qualitative research methods to produce a data description. The results indicate that the perception of each teacher of the curriculum in 2013 at Apex Senior High School has been positive. In theory, the teachers already have a good knowledge and understanding of the 2013 curriculum. History teachers' implementation of the curriculum in 2013 in the class is good enough. However, in practice, it cannot be perfect. Teachers apply the scientific approach so that almost every meeting uses discussions and lectures, though never for learning outside the classroom at the Sangiran Museum. Teachers' constraints include the need for a specialized history handbook from the government, school infrastructure that still needs improvement, socialization, and training on the curriculum. These challenges highlight the ongoing efforts required to fully integrate and optimize the 2013 curriculum in history education at Apex Senior High School, underscoring the importance of continuous support and professional development for teachers to enhance their instructional practices and enrich students' learning experiences.